On the Connectivity and Independence Number of Power Graphs of Groups - Cameron, Peter J.; Jafari, Sayyed Heidar (Graphs and combinatorics, 2020)
Let G be a group. The power graph of G is a graph with vertex set G in which two distinct elements x , y are adjacent if one of them is a power of the other. We characterize all groups whose power graphs have finite independence number, show that they have clique cover number equal to their independence number, and calculate this number. The proper power graph is the induced subgraph of the power graph on the set G - { 1 } . A group whose proper power graph is connected must be either a torsion group or a torsion-free group; we give characterizations of some groups whose proper power graphs are connected.